Penalties vs. Subsidies: A Study on Which Is Better to Promote Corporate Environmental Governance - He, Ling; Zhong, Tingyong; Gan, Shengdao; Liu, Jiamin; Xu, Chaoya (Frontiers in Environmental Science, 2022)
To reverse the trend of ecological environment deterioration, the government tries to stimulate firms to participate in environmental governance through environmental regulation. Then, which environmental regulation tools can better drive firms to carry out environmental governance activities, this needs to be corroborated by empirical studies. Using a sample consisting of Chinese A-shares listed firms from 2015 to 2019, this paper investigates the effects of two heterogeneous environmental regulation tools (environmental penalties and environmental subsidies) and their interactions on corporate environmental investment. The results show that environmental penalties have a positive impact on corporate environmental investment. Further, the heavier the penalty or the higher the administrative level of the penalty subject, the impact of environmental penalties on corporate environmental investment is more pronounced. Firms that receive environmental subsidies do not increase their investment in environmental governance. A series of robustness tests further verify that penalties have a greater impact on the environment than subsidies. Besides, it is found that environmental penalties have an environmental deterrent effect on other firms in the same industry. Our work presents evidence for the economic consequences of environmental regulation and supplements the mechanism of environmental regulation affecting corporate environmental governance. Meanwhile, this paper also provides essential guidance for the positive role of environmental penalties in driving corporate environmental governance and has important practical significance for emerging market countries to choose appropriate environmental regulation tools to promote corporate green development.